Transformative learning and the hidden dynamics of transformation. Issue 6 (1st November 2020) - Eschenbacher, Saskia
ABSTRACT: Transformative learning is 'an approach to teaching based on promoting change, where educators challenge learners to critically question and assess the integrity of their deeply held assumptions about how they relate to the world around them'. While it seems to be clear what is subject to change (assumptions), apparently it is less obvious how we can (critically) reflect on assumptions, especially since most of them operate outside of our awareness. The question that follows is: How can we bring these hidden assumptions into our awareness, so that it can be subject to change and transformation? Therefore, the purpose of this paper is threefold: We need to (1) have a more nuanced understanding of how we can help adult learners in practice to explore their 'assumptive clusters', to (2) better understand what helps or prevents learners from transforming their existing assumptions and therefore fosters or inhibits processes of transformation, and to (3) provide some concrete tools, that practitioners can use to enhance their (reflective) practice, teaching transformatively.